A novel continuous reactor with shaftless spiral for chemical looping gasification and the control of operating parameters. Issue 5 (October 2020) - Hu, Zhifeng; Wang, Mingfeng; Jiang, Enchen
Abstract: A novel continuous reactor with shaftless spiral for chemical looping gasification (CLG) of rice husk is expected to propose for application and optimal parameter. Syngas concentration, efficiency, lower heating value of syngas and micromorphology structure were investigated under different conditions of temperature, ratio of OC and rice husk (O/C) and speed. The results indicated that CLG in the shaftless spiral reactor had a better performance. The gas yield, carbon conversion efficiency and gasification efficiency were 73.33%, 63.92% and 98.26% higher than that of fixed-bed reactor, respectively. Further, higher temperature obviously enhanced gas production and efficiency but was easy to cause agglomeration and harmful to OC regeneration. Furthermore, lower O/C would increase the combustible gas production but cause a serious sintering and decrease gas production and carbon conversion efficiency. Moreover, lower speed would promote the gas production and efficiency but cause agglomeration. In addition, lower speed had a greater effect on H2 yield than CO. As a result, the shaftless spiral reactor was beneficial to CLG. The best performance with gas production of 70.99% and gasification efficiency of 67.80% was obtained in shaftless spiral reactor under the optimal parameters with temperature of 800 °C, O/C of 1.5 and speed of 5.5 r/min. Highlights: CLG of rice husk in the shaftless spiral reactor had a better performance. Higher temperature enhanced gas yield and efficiency but harmed to OC regeneration. Insufficient OC caused low gas production and deep reduction of Fe2 O3 into Fe. Lower speed would promote the gas production and efficiency but cause agglomeration. Lower speed had a greater effect on H2 yield than that of CO.